ChemInform Abstract: Palladium‐Catalyzed Dehydrogenation/Oxidative Cross‐Coupling Sequence of β‐Heteroatom‐Substituted Ketones. Issue 12 (14th March 2013) - Moon, Youngtaek; Kwon, Daeil; Hong, Sungwoo
Abstract The title sequence is studied for various heterocyclic systems such as (VII), (X), (XIII) and (XV) and leads to C‐3 functionalized systems.